A randomized controlled trial for the use of Thymus Honey indecreasing salivary gland damage following radioiodine therapy for Thyroid cancer: research protocol - Frangos, Savvas; Talias, Michael; Charalambous, Andreas (My University, 2014)
Aim: To test the effectiveness of thymus honey as a complementary intervention for decreasing the salivary gland damage due to Radioiodine (131I) therapy. Background: Radioiodine is the treatment of choice in people diagnosed with thyroid cancer following total thyroidectomy. Although its value has been acknowledged in eradicating remnant thyroid tissue and treating residual disease in patients with visible, inoperable, iodine-avid metastases, it has been associated with various salivary gland side effects. Design: This is a randomized controlled trial with a 2×3 mixed between-within subjects design. Methods: In total, 120 participants of postsurgical differentiated thyroid cancer, who will be referred to this centre for 131I therapy to ablate the remnant thyroid tissue or to treat metastatic tumour, will be prospectively studied under varying regimens of lemon candy (standard treatment) and thymus honey mouthwashes (experimental intervention). Patients will be randomized in four equally numbered groups based on the assumptions and hypothesis of the study. The recruiting process will be informed by predefined inclusion and exclusion criteria. Mixed statistical modelling will be adopted taking into consideration between and within subjects' effects and repeated measures. Discussion: The recommended intervention protocol is expected to improve the comprehensive management of salivary gland-related side effects induced by the radioiodine treatment in people diagnosed with thyroid cancer. Through the methodological approach chosen, the ideal intervention protocol in terms of the time to initiate the intervention and the frequency of the intervention to acquire optimal results in minimizing salivary glands damage will be tested.
Keywords: Nurse; Quality of life; Radioiodine; Sialadenitis; Thyroid cancer; Xerostomia